IMPLEMENTASI INOVASI APLIKASI PELAYANAN SISTEM INFORMASI PENELUSURAN PERKARA (SIPP) DI PENGADILAN AGAMA KOTA PROBOLINGGO - Septiandika, Verto; Astutik, Dita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The development of all-digital information and communication technology makes demands for public services in the implementation of government administration management. It is expected to be able to meet the needs of the community in the process of implementing public services so that innovation is needed in providing services. This study explains how the implementation of an innovative case file information service is quick, easy and can improve the effectiveness of employee performance. This study uses a qualitative research method with a descriptive approach which aims to present an overview of the Implementation of the Case Investigation Information System Service Application Innovation (SIPP) at the Probolinggo Religious Court. And data collection techniques through direct observation, interviews with sources and documentation with several related parties. Based on the results of this study, that the implementation of the case tracking information system (SIPP) service application has been running efficiently in case file administration activities that can be easily accessed by internal and external parties through the website, it's just that not a few external parties from the community do not fully understand in the implementation to obtain information related to the case so that there is a need for organizational participation in providing understanding in the implementation of information services through the SIPP application. In this process, it is necessary to hold socialization or assistance in accordance with the Standard Operating Procedure (SOP) in providing services through the Case Investigation Information System (SIPP) application which can be accessed through the website page without coming directly to the Probolinggo Religious Court office.